Penyuluhan Tentang Perawatan Payudara Pada Ibu Hamil Di Desa Labuhan Rasoki: Breast Care, Pregnant Women - Dewi, Sri Sartika Sari (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
Pregnancy is an exciting time for prospective parents and families. Prospective parents, especially prospective mothers, need to have the knowledge and readiness to conceive, give birth and breastfeed their children. In the antenatal period, pregnant women must be prepared both physically and psychologically to care for their babies. A good antenatal care is to pay special attention to the preparation of the breast and nipple in anticipating the problem of giving breast milk to the baby. The implementation of PKM begins with coordination with KIA officers to contact posyandu cadres and pregnant women who will be participants in the activity. This counseling activity was carried out in 1 meeting. Participants in this activity amounted to 23 pregnant women. Counseling is done by gathering pregnant women who are in Labuhan Rasoki Village, Southeast Padangsidimpuan District, Padangsidimpuan City in one rather large room. During the implementation of the activities, the participants were always enthusiastic and enthusiastic in participating in the series of activities. The counseling activities carried out The counseling activities carried out ran smoothly. This is evidenced by the enthusiasm of pregnant women in carrying out counseling activities in an orderly and orderly manner.